Commentary to F-GP1, a Novel PET Tracer Designed for High-Sensitivity, Low-Background Detection of Thrombi: Imaging Activated Platelets in Clots—Are We Getting There? - Andrew W. Stephens MD, PhD; Norman Koglin PhD; Ludger M. Dinkelborg PhD (Molecular Imaging)
Thrombus formation can lead to heart attacks, stroke and pulmonary embolism, which are major causes of mortality. Current standard diagnostic imaging methods detect anatomic abnormalities such as vascular flow impairment but have limitations. By using a targeted molecular imaging approach critical components of a pathology can be selectively visualized and exploited for an improved diagnosis and patient management. The GPIIb/IIIa receptor is abundantly and specifically exposed on activated platelets and is the key receptor in thrombus formation. This commentary describes the current status of GPIIb/IIIa-based PET imaging approaches with a focus on the recently published preclinical data of the small-molecule PET tracer 18 F-GP1. Areas of future research and potential clinical applications are discussed that may lead to an improved detection of critical thromboembolic events and an optimization of available antithrombotic therapies by tracking activated platelets.